THE USE OF A TECHNOLOGICAL SYSTEM OF MEASURE TO ANALYZE THE VARIABILITY IN THE EXECUTION OF TENNIS SERVICE AND THE EVALUATION OF ITS RESULT (Fiep Bulletin - online, 2014)
Through this study, we present a measurement protocol to analyze kinematics variables that affect to variability and precision in the performance of a sport skill like the tennis service. From the knowledge generated in this previous analysis, we will analyze how are influenced different variables as ball speed and perturbations caused during the movement in trajectory of executing arm, on motor pattern consistency and precision reached in strokes. Thus, in this document, we presented a developed technological protocol to collect the referred data about the mentioned variables, with the purpose of having optimized and validated instruments applied to reliable collection of the parameters specified in our study.
Keywords: variability; consistency; kinematics analysis